Septal Extender 2024: A Holistic Approach in Congenital, Reconstructive, and Aesthetic Nasal Surgery—Current Status, Criteria, and Guidelines - Lema Balla, Juan Carlos; Sánchez Espinoza, Alisson Nicole; Quesada Chica, Juan Francisco; Ocapana Taco, Pamela Nicole; Lema Balla, José Roberto (Arandu UTIC, 2025)
Introduction: The Septal Extender 2024 has emerged as a pivotal innovation in nasal surgery, with applications spanning congenital, reconstructive, and aesthetic domains. Objective: To provide a comprehensive review of the evolution, clinical criteria, and guidelines for the use of the Septal Extender 2024 in various nasal surgery contexts. Methods: A systematic review of recent literature indexed in Scopus, combined with retrospective analysis of clinical cases, was conducted to evaluate outcomes, complications, and best practices. Results: The use of the Septal Extender 2024 has demonstrated significant improvements in both functional and aesthetic outcomes. Innovations in biocompatible materials and surgical techniques have reduced complication rates and improved patient satisfaction. Conclusions: The Septal Extender 2024 represents a robust and versatile tool in modern rhinoplasty, with clear guidelines for patient selection and perioperative management enhancing its safety and efficacy.